Analisis Laporan Keuangan Perusahaan Menggunakan Rasio Likuiditas Pada PT. Indofood Suksess Makmur TBK Tahun 2020-2021 - Atmim Nurona Nurona; Khubib Miftakhul Amin; Adelina Citra Dewi (JAF (Journal of Accounting and Finance), 2023)
Financial reports aim to provide company information on financial performance, financial position, and financial position that can change, these parties really need information that aims to make and determine decisions. The company's financial position is influenced by controlled resources, financial structure, liquidity and solvency, in order to be able to adapt to a frequently changing environment. The current ratio from year to year is below the standard value of 200%. In 2020 the current ratio of 95.0% can be said to be not good, then it will increase in 2021 to 193.6% because current assets are larger and can be said to be good. Based on the quick ratio of PT. Indofood Sukses Makmur Tbk in 2020-2021 is categorized as quite good because it has not yet reached the industry standard of 67.4% and every year it experiences the same increase and stability as the current ratio. Next is the result of the cash ratio of PT. Indofood Sukses Makmur Tbk in 2020 of 42.8% can be said to be good because it is below the 2021 standard which is categorized as very good and the company has been able to pay off its longterm debt using the availability of cash and cash equivalents. Keywords: Financial Reports, Liquidity Ratio, Industry Standard